Transformation of Business Strategies for Art Galleries in The Industry 4.0 Era : Embracing The Digital Trend and Economic Impact - Anjasyadeva, Gede Bagus Rahadhe; Maradona, Agus Fredy (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research was conducted at a painting gallery in Bali with the aim of finding answers about the adoption of digital transformation in the development of business strategies in the Industrial Era 4.0. The method used is a qualitative method using data collection techniques in the form of in-depth interviews and field observations. Interviews were conducted with 6 informants as gallery owners/managers/staff and gallery visitors. The results found that the digital transformation carried out is still limited using social media for product marketing, AR and VR technology is still very limited considering the cost limitations. Using technology, especially social media, helps marketing effectiveness and expands the market. However, on the one hand, there are concerns that digital transformation will erode the value of traditional arts and culture. So what needs to be emphasized is the proper use of technology to continue to support the introduction of existing art and culture.